Um estudo sociodiscursivo da temática do preconceito contra negros em sentenças de injúria racial - Ariana de Carvalho (2020)
This study aims at the discourse of judgments that decide at the trial court level racial insult cases. We are interested in verify how prejudice against blacks has been treated from the legal point of view and whether or not such judgments are in line with the seeking for a society based on mutual respect. We aimed in a specific way to find out, through the observation of linguistic-discursive resources handled by magistrates, if they keep loyal to the principles and legal rules in the judgments' motivations and, if they are ethical, impartial and cautious in assessing the evidence to make the final decision. We also seek to observe if the attitude of these professionals is of engagement or distancing in relation to the theme (imposed) of racial insult and, consequently, how they fit into the discursive formation (FD) that seeks to combat racial prejudice. This research corpus consists of seven judgments, which 3 were convicting, 3 acquittals and 1 partial condemnatory, collected on the TJMG website, from the 2nd semester of 2016 by the end of 2017. In order to achieve our goals, we used the French Discourse Analysis as the main theoretical basis (ADF), centered on the proposal of a Global Semantics developed by Maingueneau (2008a), from which we took five levels as categories to analyze the judgments: intertextuality, vocabulary, cohesion, enunciation mode and themes. We related these plans to other notions and approaches that fit the ADF to complement and enrich our analysis mechanism. After analyzing each sentence and making comparisons between them, we concluded that, in the three condemnatory judgments, the speakers / magistrates were cautious in their motivations, loyal to the legal system and impartial in the analysis of the evidence, demonstrating an attitude of engagement with the FD that interprets the racial prejudice as a sensitive issue and a crime to be combatted with commitment. On the other hand, we identified flaws in the motivation of two acquittal judgments and in the partial condemnatory. In these cases, the speakers / magistrates, in different ways, impaired what the Ethics Code of the National Magistracy and what the Constitution itself advocated, not approaching the issue with sufficient care, which leads us to affirm that they behaved in a negligent way and not engaged with the FD to combat racial prejudice. The analysis and comparison of the judgments allowed us to prove that there may be flaws in our legal system and that this is a problematic issue if we think that the magistrates have an exemplary and educational role. Furthermore, considering the legislative separation of racial prejudice and racism, we see how the legal mechanism can be at the service of maintaining the status quo, which makes it difficult to seek for a fairer society with less color prejudice.